Language and Emotion: The Communication Pattern on the Result of Central Jakarta Governor Election on Online Newspaper - APRILANITA, RAHMAWATI (LPPM Universitas Mercu Buana Yogyakarta, 2018)
The present study aims at observing and presenting the types of language features used by Indonesian adults commenting on an online news using English as their foreign language to know whether Indonesians tend to be blunt or mitigate in expressing their feeling on the results of central Jakarta governor election. The comments uttered were their reaction and expression on the result of Central Jakarta Governor Election. The data observed was taken from all comments on a headline of online newspaper. The comments were from 74 people.The findings are generated based on quantitative calculation on the major verb used to express the feelings.